Economic Geology Models 2. Melt Inclusions of Native Silver and Native Bismuth: A Re-examination of Possible Mechanisms for Metal Enrichment in Five-Element Deposits - Marshall, Dan (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2008)
SUMMARY This paper presents preliminary observations on veinlets and trails of native bismuth and silver melt inclusion that cross-cut silicate and carbonate vein fill and alteration minerals in the five-element veins at Cobalt, Canada. The low melting temperature of bismuth (271°C) is consistent with the current estimates of vein formation at Cobalt, and melt textures are displayed in native bismuth inclusions and trails. Native silver displays identical textures and these are also interpreted to have formed from a melt. However, native silver melts above 950°C, which is in direct conflict with current estimates of silver deposition within the Cobalt camp. In light of the similarities in textures, existing temperature evidence, the lack of experimental studies in the Co–As–Ag ternary, and recent advances in the study of melt inclusions in sulfide deposits, the native silver textures are also interpreted to have formed at temperatures as low at 350°C. A primary three-phase fluid inclusion assemblage contained within growth-zoned quartz crystals in the granophyric phase of the Nipissing diabase was chosen as representative of the highest temperature fluids responsible for ore deposition at Cobalt. This fluid inclusion assemblage displays microthermometric behaviour similar to the hypersaline fluid inclusions previously determined as the transporting medium for the silver mineralization at Cobalt and are consistent with depositional temperatures of about 350°C. These temperatures, although sufficient to produce melt inclusions of native bismuth, are insufficient to melt silver. Petrography and solid inclusion textures are consistent with metallic silver melts, indicating that Ag–Sb–Hg ternary or more complex silver-bearing systems containing H2O, H2S and salts may have eutectics at temperatures below 350°C. This is interpreted as a potential mechanism for silver mobilization and enrichment, and has potential applications to other types of vein mineralization.